Evaluation of ECG Interpretation Systems: Signal Analysis - Zywietz, Chr.; van Bemmel, J. H.; Degani, R. (Methods of Information in Medicine, 1990)
Performance analysis of biosignal processing systems which provide diagnostic statements requires particular care. Besides general accuracy requirements, psychological and legal implications for patient and physician have to be considered on both the development and the user sites. Cybernetics and control engineering have provided the basic methodology for performance analysis of systems: in technical systems often mathematically defined functions and signals can be fed into the system to be tested and its response and output provide the necessary performance characteristics after adequate mathematical analysis. For systems which process biosignals, as for example ECG analysis systems, instead of analytically given signals learning and test sets of data derived from patients have to be applied. The performance analysis is done on a statistical basis. In this paper construction and composition of learning and test data sets as well as methods for performance evaluation of the signal pocessing part of ECG programs are described. Specific reference is made to the European project Common Standards for Quantitative Electrocardiography (CSE) where ten ECG- and nine VCG-programs have been tested. The results of these tests provide reference data and standards for further program development as well as for independent system performance evaluation.
Keywords: ECG System Testing; Measurement Performance; Validation; Signal Processing